AMOBILISASI PEKTINASE DARI Bacillus firmus MENGGUNAKAN MATRIKS OPP (OXIDIZED POLYPROPYLENE)-KITOSAN - Sari, Ayunda Arum; Roosdiana, Anna; Mardiana, Diah (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
A Pectinase is an enzyme that can hydrolyze pectin compounds into galacturonic acid. In order to enhance the pectinase efficiency, the enzyme can be immobilized in certain matrix. The pectinase was isolated from Bacillus firmus, and then purified with ammonium sulphate with 20-60% saturated level, followed by dialysis. The aims of the research were to determine the optimum conditions of immobilized pectinase by physical adsorption on oxidized polypropylene (OPP) coated chitosan, which included the shaking time and enzyme concentration. Initial protein used for immobilizing free pectinase was 1.367 mg/mL and the activity was 241.1 units. The results showed that the optimum condition of pectinase immobilization was achieved on shaking time of 3 hours and pectinase concentration of 1.094 mg/mL with amount of pectinase adsorbed at 53,98 mg/g within activity of 220.2 units.